المدرسة الجزائزية ودورها في تنمية الجانب المهني لدى التلميذ - سالمي, مسعودة (University of Eloued جامعة الوادي, 2020)
Through this intervention, we will learn how to develop the professional side of students within the Algerian school by identifying the guidance and vocational guidance practiced in the three stages of primary, intermediate and secondary education in order to narrow the gap between the outputs and requirements of the labor market. The intervention will first talk about the school and its functions in general and we will highlight the Algerian school in its three stages of primary, intermediate and secondary. Secondly, we look at vocational guidance in schools
الملتقى الوطني الأول حول المدرسة الجزائرية الإشكالات والتحديات 18- 19 فيفري 2020. جامعة الوادي
Keywords: المدرسة الجزائرية؛ التوجيه المهني.